Characterization of bronchiectasis in the elderly. (October 2016) - Bellelli, Giuseppe; Chalmers, James D.; Sotgiu, Giovanni; Dore, Simone; McDonnell, Melissa J.; Goeminne, Pieter C.; Dimakou, Katerina; Skrbic, Dusan; Lombi, Andrea; Pane, Federico; Obradovic, Dusanka; Fardon, Thomas C.; et al.
Abstract: Introduction: Although bronchiectasis particularly affects people ≥65 years of age, data describing clinical characteristics of the disease in this population are lacking. This study aimed at evaluating bronchiectasis features in older adults and elderly, along with their clinical outcomes. Methods: This was a secondary analysis of six European databases of prospectively enrolled adult outpatients with bronchiectasis. Bronchiectasis characteristics were compared across three study groups: younger adults (18–65 years), older adults (66–75 years), and elderly (and ≥76 years). 3-year mortality was the primary study outcome. Results: Among 1258 patients enrolled (median age: 66 years; 42.5% males), 50.9% were ≥65 years and 19.1 ≥ 75 years old. Elderly patients were more comorbid, had worse quality of life and died more frequently than the others. Differences were detected among the three study groups with regard to neither the etiology nor the severity of bronchiectasis, nor the prevalence of chronic infection with P. aeruginosa . In multivariate regression model, age (OR: 1.05; p-value: <0.0001), low BMI (OR: 2.63; p-value: 0.02), previous hospitalizations (OR: 2.06; p-value: 0.006), and decreasing FEV1 (OR: 1.02; p-value: 0.001) were independent predictors of 3-year mortality, after adjustment for covariates. Conclusion: Bronchiectasis does not substantially differ across age groups. Poor outcomes in elderly patients with bronchiectasis might be directly related to individual's frailty that should be further investigated in clinical studies. Highlights: Among adult patients with bronchiectasis more than 50% are over 65 years. Oldest patients have an increased comorbidity level, experience a worse quality of life and die more frequently. No age-related differences for bronchiectasis severity, signs/symptoms, systemic flogosis and chronic Pseudomonas infection.